Pengaruh Kualitas Produk, Promosi dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Melalui Keputusan Pembelian Pelanggan Minimarket Alfamart Ruko Beryl Gading Serpong - Chandra, Ray; Setiyowati, Harlis (Manajemen dan Kewirausahaan, 2024)
Alfamart is a minimarket owned by PT Sumber Alfaria Trijaya TBK and has branches in almost all provinces of Indonesia. This research aims to determine the influence of product quality, promotion and service quality on customer loyalty through purchasing decisions of Alfamart Ruko Beryl Gading Serpong minimarket customers. The research method used in this research is a quantitative method which is ex post facto in nature where the data is collected using a questionnaire and then manages the data and the analysis used is descriptive analysis. The quantitative research method in this study was carried out to test the influence of product quality, promotion and service quality on customer loyalty through purchasing decisions of Alfamart customers in the Serpong area. The Quality and Service Quality variables have a significant positive effect on the respondents' customer loyalty. The variable that does not have a positive effect on customer loyalty is the Promotion variable. The variable that has the highest significant positive influence on customer loyalty is Product Quality with an R-Square test value of 0.762 and an F-Square test result of 0.872.